Communicating information on maize hybrids through leaflets: What works from a farmer’s perspective? - Kitoto, Victor O.; Rutsaert, Pieter; Donovan, Jason A.; Kariuki, Sarah K. (CGIAR, 2024)
To successfully market new seed products, seed companies need to effectively communicate product attributes and performance details to farmers. Seed leaflets are a very popular method used by maize seed companies in Kenya. However, there is no existing knowledge on how farmers perceive seed leaflets or insights into best practices for seed companies to effectively inform farmers about new seed products. Using the hybrid maize seed product market in Kenya as a case study, this brief looks at the effectiveness of seed product leaflets in transmitting information to farmers. In 2023, we conducted a farmer survey (n=646) and focusgroup discussions (n=10) in Machakos County to understand what farmers expect from leaflets and how they evaluate leaflets currently used by seed companies. While farmers have a high interest in leaflets, availability of leaflets was limited at points of sale. Our interactions with farmers brought to light multiple opportunities for improvement in leaflet design, both in layout and language as well as in the content that should be included in the leaflets. We highlight the role the public sector can play in helping farmers make better informed decisions on seed choice.